Effect of Blood Sampling Site on the Changes in the Physiological Indices of Preterm Infants: A Crossover Clinical Trial - Zahra Pourashoori; Keyvan Mirnia; Fatemeh Ghorbani; Abdolrasoul Safaiyan; Mohammad Ali Nematzadeh; Mohammad Arshadi Bostanabad (Mashhad University of Medical Sciences, 2018)
Background: Venipuncture is one of the most painful and common interventions in Neonatal ward. A preterm infant can not cope long-lasting physiologic stresses; therefore, the pain caused by blood sampling may change the infant's physiologic responses to the stress. This present study aim is to investigated and compare physiologic changes (pulse rate and oxygen saturation) in two sites of blood sampling in preterm infants. Methods: This crossover clinical trial was performed on 105 preterm infants of 28-32 weeks' gestational age in Tabriz Alzahra teaching hospital. Infants were selected through convenient sampling method and were allocated to two groups using doubleblock. In group 1(53 infants): the blood was first drawn from head veins and after a 24-hour interval, it was repeated at the back of the hand. In group 2 (52 infants): this procedure was implemented conversely.Infants' demographic variables and physiologic values(pulse rate and oxygen saturation) were measured in both sampling methods. The data were analyzed using SPSS.13, Paired t-test and Friedman test. P˂ 0.05 was considered as significant. Results: There was a significant difference between two groups considering infants' age and various assessing timeswhen pulse rate changeswere investigated (Pv≤0.001);however, no significant difference was found regarding toblood sampling sites(head & back of the hand)).In addition, no significant difference was found in oxygen saturation changes in terms of age and blood sampling sites(head& back of the hand); however, these changes were significantly different in terms of different blood sampling times (PvTIME≤ 0.001). Conclusion: Pulse rate and oxygen saturation changingwas not significantly different in two methods of blood sampling from head veins and back of the hand veins in preterm infants; therefore, both sites can be used for drawing blood. During blood sampling in preterm infants of lower gestational age, the rate of pulse increased;however, the level of oxygen saturation decreased. As a result, since infants of lower gestational age are more vulnerable, drawing blood is required to be performed at the first attempt and no more attempts should be made